Occupational Disruptions Among Health Professional Faculty During COVID-19 Pandemic - Supawadee C. Lee; Mahrukh Awan; Uruj Chaudhary; Priyanka John (Open Journal of Occupational Therapy, 2022)
The coronavirus disease was an unexpected pandemic. It led faculty in the health professional graduate programs to adjust and adapt to the new reality, which impacted them mentally, physically, and emotionally, and disrupted their occupational performance. The purpose of this phenomenological study was to examine the impact of COVID-19 on occupational engagement through semi-structured interviews conducted to understand the lived experiences of graduate faculty in health professional programs at one university in the northeast region. The interviews were analyzed by creating codes and themes through the process of peer debriefing. Eight faculty participated in the study, including faculty from the following departments: Nursing, Communication and Science Disorders, Occupational Therapy, and Nutrition and Dietetics. The results suggest that the COVID-19 pandemic caused both positive and negative impacts on the participants’ occupational engagement. Five themes emerged: impacted sleep routines, adaptation, stress and anxiety, outdoor activities, and parental and work responsibilities. These findings can guide colleges and universities to prepare and provide the right support and resources to reduce stress and anxiety and promote occupational engagement of the faculty in the future. The findings also help to identify the roles of occupational therapists in times of disasters or a pandemic in preparedness, plans for resources, improving faculty’s occupational engagement and occupational balance, and rebuilding their routines.